2014
DOI: 10.1186/1297-9716-45-31
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of environmental MRSA at an equine teaching hospital: introduction, circulation and maintenance

Abstract: The role that environmental contamination might play as a reservoir and a possible source of Methicillin-resistant Staphylococcus aureus (MRSA) for patients and personnel at equine veterinary hospitals remains undefined, as the environment has only been monitored during outbreaks or for short periods. Therefore, the objectives of this study were to determine the monthly presence, distribution, and characteristics of environmental MRSA at an equine hospital, and to establish patterns of contamination over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…We estimated the prevalence of lukPQ in an international collection of equid S. aureus isolates (The Netherlands (unpublished), Austria17, the United States18, Sweden19, Portugal20, Italy21 and Spain22) using a PCR assay to identify the three prophage-encoded leukocidins ( lukSF-PV, lukMF’ and lukPQ ). lukPQ was present in 29 out of 194 strains (15%, 95% CI: 10 to 21%) from the Netherlands, Italy and Portugal, whereas lukSF-PV and lukMF’ were only found once and twice, respectively (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated the prevalence of lukPQ in an international collection of equid S. aureus isolates (The Netherlands (unpublished), Austria17, the United States18, Sweden19, Portugal20, Italy21 and Spain22) using a PCR assay to identify the three prophage-encoded leukocidins ( lukSF-PV, lukMF’ and lukPQ ). lukPQ was present in 29 out of 194 strains (15%, 95% CI: 10 to 21%) from the Netherlands, Italy and Portugal, whereas lukSF-PV and lukMF’ were only found once and twice, respectively (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus regularly causes problems in equine hospitals, leading primarily to joint, skin and wound infections27. Patient-to-patient transmission and outbreaks within equine hospitals as well as zoonotic transmission have been documented1819282930. Recently, an epidemic subclone of CC398 MRSA was shown to have spread within and between equine hospitals23.…”
Section: Discussionmentioning
confidence: 99%
“…Since that outbreak, passive surveillance, in which we test horses in which MRSA infection is suspected, was continued, and, in each case of postoperative wound infection in a horse, a swab was sent for culture and antimicrobial susceptibility testing. Reappearance of MRSA in samples collected from horses and personnel in the veterinary teaching hospital was not unexpected, as it has been demonstrated that MRSA is constantly introduced and frequently found in an equine veterinary hospital environment (18). Among the MRSA strains that have been described are ST8 (Canadian MRSA-5/USA-500 epidemic MRSA strain) and ST254, which are suggested to be horse adapted (19).…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, MRSA has become one of the most important nosocomial pathogens affecting equine veterinary hospitals (18). The cross-transmission of MRSA between hospitalized horses and veterinary staff in the 2010 outbreak at our hospital (8) resulted in increased awareness of this pathogen among hospital personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation